Heterochronic development of pelvic fins in zebrafish: possible involvement of temporal regulation of pitx1 expression - Pratiwi, Hilda Mardiana; Hirasawa, Masahiro; Kato, Kohki; Munakata, Keijiro; Ueda, Shogo; Moriyama, Yuuta; Yu, Reiko; Kawanishi, Toru; Tanaka, Mikiko (Frontiers in Cell and Developmental Biology, 2023)
Anterior and posterior paired appendages of vertebrates are notable examples of heterochrony in the relative timing of their development. Teleost fishes have posterior paired appendages, pelvic fin buds, that emerge much later than their anterior paired appendages, pectoral fin buds. Pelvic fin buds of zebrafish (Danio rerio) appear at 3 weeks post-fertilization (wpf) during the larva-to-juvenile transition (metamorphosis), whereas pectoral fin buds arise from the lateral plate mesoderm on the yolk surface at the embryonic stage. Here we explored the mechanism by which presumptive pelvic fin cells maintain their fate, which is determined at the embryonic stage, until the onset of metamorphosis. Expression analysis revealed that transcripts of pitx1, one of the key factors for the development of posterior paired appendages, became briefly detectable in the posterior lateral plate mesoderm at early embryonic stages. Further analysis indicated that the pelvic fin-specific pitx1 enhancer was in the poised state at the larval stage and is activated at the juvenile stage. We discuss the implications of these findings for the heterochronic development of pelvic fin buds.